Revitalisasi Makanan Fermentasi Tradisional Kuantan Singingi melalui Pelatihan Berbasis IPTEKS - Ismawati Ismawati; Saryono Saryono; Mukhyarjon Mukhyarjon; Enikarmila Asni; Silvera Devi; Suci Anggraini; Nabella Suraya; Lunari Kesya; Dinda Salsabila; Cantika Natswa Deanra (Unri Conference Series: Community Engagement, 2025)
Malnutrition, especially among children under five, remains a significant public health concern in Indonesia, including Riau Province. One potential effort to address this issue is the utilization of traditional fermented foods from Kuantan Singingi Regency, such as pekasam, sarobuong, puduong, and cangkuok semaung. These foods are rich in nutrients, including protein, carbohydrates, amino acids, minerals, and probiotics beneficial to health; however, they are on the verge of extinction.This community service program aimed to revitalize traditional Kuansing fermented foods through a science and technology-based training approach. The program implementation involved video demonstrations of traditional food preparation, distribution of pocket books, and interactive discussions with health cadres, as well as pregnant and breastfeeding mothers, and mothers with toddlers.The results showed high enthusiasm among participants, demonstrated by their active involvement in discussions and question-and-answer sessions. The training not only improved participants’ knowledge but also fostered awareness and a sense of ownership of local food, while simultaneously opening opportunities for small-scale household businesses.